Educação de surdos em Mato Grosso do Sul : desafios da educação bilíngue e inclusiva - Quiles, Raquel Elizabeth Saes (2015)
Deaf education, the object of this research, stands today as a field of study that leads to the reflection of school spaces, especially regarding to its form of organization and pedagogical practices in action. Under the scope of Special Education policies, the proposition of the Ministry of Education for deaf education fits into the paradigm of inclusive education, which comprises the common mainstream education as a privileged locus of insertion. On the other hand, which does not necessarily mean the other way, the education of deaf should be discussed in a bilingual proposition, considering the linguistic singularities of deaf people. In the tensions, limits and possibilities between these two educational proposals (inclusive education and bilingual education) lies this work, which aimed to highlight the proposal for deaf education in the state of Mato Grosso do Sul in order to identify its lineation in a polo school for deaf people focusing on bilingual education in the context of inclusive education. The particularity of this research is the experiences of a school reality that addresses itself as bilingual. To achieve the perceptions about this school, as methodological procedures, the analysis of national and state documents comprising the Special Education policy and speeches, through interviews managers, teachers, educational interpreters, students and deaf instructor were used. The data were interpreted, considering the historical-cultural approach, from two main categories: language and enunciation, understood through studies of Vygotsky and Bakhtin. To do so, they were organized through sub-themes that permeate discussions of inclusive education (organization of the Special Education services, socialization and schooling) and bilingual education (bilingual condition of deaf students, school practices of the common classroom and training of the professionals of education). The school searched was not fully inclusive, with many problems in this direction, and neither bilingual at all, since the sign language does not occupy central place in school activities. Fundamentally, it was identified the absence of a collective project involving professionals in the school assistance for deaf students – each professional does what s/he can and how s/he can. In conclusion, the debate on educational proposals that are meaningful for the deaf leads to a (dis)structuring of school spaces toward a proposition that contemplates primarily the sign language. The intersection between inclusive education and bilingual education enables a rethinking of the school aiming its transformation. If the school is bilingual, centralizing sign language in all routes and processes, deaf students are more likely to participate and learn approaching them, in fact, to the assumptions of inclusive education.